Global Trends In The Learning Process Of Pancasila And Citizenship Education In Schools - Aina Aina; Syalwa Marliza; Salsabila Husna Pulungan; Rahmansyah Fadlul Al Karim Rambe (International Journal of Cultural and Social Science, 2024)
The use of social media for the younger generation can increase interaction between users without being limited by distance and time. The ease of interaction has an impact by making it easier to communicate both conveying news/messages and responding in the form of criticism or suggestions. One of the negative impacts that can occur is conveying a message in the form of an invitation to instill hate speech related to the life of the nation and state. The study was conducted to examine the influence of social media on national insight in the younger generation UINSU, Sumatera Utara. Survey research with the independent variable (X) namely social media and the dependent variable (Y) namely national insight. Based on the results of the data processing obtained a significance (Sig) of 0.020 <0.05 so it is concluded that social media (X) has an effect on national insight (Y).